The Challenges in Inculcating Islamic Values in the National Educational System in the Era of Globalization: A Case-Study at a Private Secondary School - Mardiani, Ade; Ismail, Halim bin; Ahmad, Ismail Sheikh (IJECA (International Journal of Education and Curriculum Application), 2023)
Globalization has a strong impact on the world of education. it needs to consider the best solutions that can be implemented so that the National Educational System (NES) can play the role and function it should. The process of reformulating educational policies must pay attention to Islamic values, which are the beliefs of most of society in Indonesia. The purpose of this research is to investigate the challenges to the inculcation of Islamic values in the National Educational System (NES) in the era of globalization. Qualitative research was adopted as the method in this study. Five school authorities and five teachers with more than fifteen years of experience were interviewed in semi-structured interviews. Previous research found that teachers faced many problems in inculcating Islamic values, such as in the process of teaching and learning, curriculum, methods of teaching, and so on. The limitation of previous research was most of the problems in the process of teaching and learning only. Here we report the problems that become challenges in inculcating Islamic values in the NES in the era of globalization. The challenges are the national curriculum, parents’ lack of support, students’ diverse backgrounds, and the pandemic scenario of COVID-19. Therefore, school authorities and teachers should try continuously to provide the best education to students, such as innovation and evaluation in teaching and learning both related to subjects in the national curriculum, and the activities in instilling Islamic values. Additionally, it needs good cooperation with various parties like the government, parents, and students.